Pembingkaian Konflik Palestina oleh Al Jazeera.com: Perspektif Islam terhadap Dominasi Narasi Global - Yudiyanto, Ade Rachmat; Sazali, Hasan (Islam & Contemporary Issues, 2025)
This study explores how Al Jazeera.com frames the Palestine-Israel conflict as part of a broader resistance to dominant global narratives. It focuses on themes of justice, victimhood, and Islamic identity. Using Critical Discourse Analysis (CDA) a method developed by Norman Fairclough to examine how language reflects and shapes power dynamics the research analyzes 15 news and opinion articles published during two key periods of heightened conflict: May 2021 and October 2023. The analysis reveals that Al Jazeera consistently presents the conflict not as a balanced clash between equal sides, but as an unequal struggle in which Palestinians face systemic oppression. The platform uses strong terms such as “occupation,” “apartheid,” and “resistance” to highlight this imbalance. Islamic elements appear frequently, both symbolically (e.g., references to the Al-Aqsa Mosque) and conceptually (e.g., calls for ummah, or global Muslim solidarity). The study concludes that Al Jazeera acts not just as a media outlet but also as a discursive agent—shaping public opinion and challenging dominant Western perspectives. The novelty of this study lies in its integration of Islamic worldview and Global South positioning into media discourse analysis of the Palestine-Israel conflict.